Social attitudes to the deforestation of tropical rainforests - Trempała, Wojciech; Sadowski, Sławomir (Studia Ecologiae et Bioethicae, 2018)
The article presents the findings of research on attitudes of man toward the problem of destroying of tropical rainforests. The empirical measurement was obtained in the years 2014–2015 from a representative sample of 1,000 inhabitants of Kuyavian-Pomeranian Voivodeship. The respondents were asked to take a stance toward four statements which express approval or disapproval of the clearance of rainforests. Axiologically and normatively, the statements were adjusted either to anthropocentrism or biocentrism, which results from the division accepted in environmental ethics. The results indicate that a substantial majority of the respondents reject individualistic anthropocentrism, according to which rainforest clearance may be justified by the welfare and interests of particular individuals. Simultaneously, they give their full approval for biocentrism statements whose content voices an objection against the destructive impact of humans on the functioning of the tropical jungle. Most respondents allow for the clearance of tropical rainforests only when it serves the interests of the whole society and future generations.